An assessment of how the properties of pyrochar and process thermodynamics impact pyrochar mediated microbial chain elongation in steering the production of medium-chain fatty acids towards n-caproate. (August 2022) - Wu, Benteng; Lin, Richen; Ning, Xue; Kang, Xihui; Deng, Chen; Dobson, Alan D.W.; Murphy, Jerry D.
Graphical abstract: Highlights: Optimal pyrochar addition improved the n-caproate yield by 115%. An ethanol to acetate molar ratio of 2 mol/mol achieved the highest MCFA yield. Potential cytotoxicity led by excess graphene addition was imposed on the microbes. Pyrochar addition led to an energy benefit of 93.50 kJ/mol reaction. Microbes affiliated with Rummeliibacillus and Aminivibrio may play a critical role. Abstract: Microbial chain elongation fermentation is an alternative technology for medium-chain fatty acid (MCFA) production. This paper proposed the addition of pyrochar and graphene in chain elongation to improve MCFA production using ethanol and acetate as substrates. Results showed that the yield of, and selectivity towards, C6 n-caproate were significantly enhanced with pyrochar addition. At the optimal mass ratio of pyrochar to substrate of 2 g/g, the maximum n-caproate yield of 13.67 g chemical oxygen demand/L and the corresponding selectivity of 56.8% were obtained; this represents an increase of 115% and 128% respectively as compared with no pyrochar addition. Such improvements were postulated as due to the high electrical conductivity and surface redox groups of pyrochar. The optimal ethanol to acetate molar ratio of 2 mol/mol achieved the highest MCFA yield under pyrochar mediated chain elongation conditions. Thermodynamic calculations modelled an energy benefit of 93.50 kJ/mol reaction for pyrochar mediated n-caproate production.